Association of molecular subtype concordance and survival outcome in synchronous and metachronous bilateral breast cancer. (June 2021) - Ding, Shuning; Sun, Xi; Lu, Shuangshuang; Wang, Zheng; Chen, Xiaosong; Shen, Kunwei
Abstract: Background: The aim of this study was to analyze the association of molecular subtype concordance and disease outcome in patients with synchronous bilateral breast cancer (SBBC) and metachronous breast cancer (MBBC). Patients and methods: Patients diagnosed with SBBC or MBBC in the Surveillance, Epidemiology, and End Results (SEER) database or Comprehensive Breast Health Center (CBHC) Ruijin Hospital, Shanghai were retrospectively reviewed and included. Clinicopathologic features, molecular subtype status concordance, and prognosis were compared in patients with SBBC and MBBC. Other prognostic factors for breast cancer-specific survival (BCSS) and overall survival (OS) were also identified for bilateral breast cancer patients. Results: Totally, 3395 and 115 patients were included from the SEER and Ruijin CBHC cohorts. Molecular subtype concordance rate was higher in the SBBC group compared to MBBC in both SEER cohort (75.8% vs 57.7%, p < 0.001) and Ruijin CBHC cohort (76.2% vs 45.2%, p = 0.002). Survival analyses indicated that SBBC was related to worse BCSS than MBBC (p = 0.015). Molecular subtype discordance was related to worse BCSS (hazard ratio (HR), 1.64, 95% confidential interval (CI), 1.18–2.27, p = 0.003) and OS (HR, 1.59, 95% CI, 1.24–2.04, p < 0.001) in the SBBC group, but not for the MBBC group (p = 0.650 for BCSS, p = 0.669 for OS). Conclusions: Molecular subtype concordance rate was higher in the SBBC group than MBBC group. Patients with discordant molecular subtype was associated with worse disease outcome in the SBBC patients, but not in MBBC, which deserves further clinical evaluation. Highlights: SBBC was associated with higher concordance rates of ER, PR, HER2, and molecular subtype status compared to MBBC. SBBC had worse BCSS than MBBC. Molecular subtype discordance was independently related to worse prognosis in SBBC but has no impact on prognosis of MBBC.